Kebutuhan Informasi Masyarakat Kecamatan IV Jurai Kabupaten Pesisir Selatan - Rini, Rini; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
The purpose of this paper is to describe: (1) The information required by the District IV Jurai South Coastal District, (2) inhibiting factors that affect the public in obtaining information, (3) the efforts made to obtain the information. The data source of this study is that oral sources told directly by informants as the original speakers. Data were collected through observation and interviews with the District IV Jurai South Coastal District. Analyzing the data be descriptive, outlining the findings or research data in accordance with the activities undertaken during Field Work Practice in the Office of Libraries, Archives and Documentation South Coastal District. Keywords: information needs